Nilai-Nilai Pendidikan Karakter dalam Kitab ‘Izhâtun Nâsyi’în karya Syekh Musthafa Al-Ghalayain dan Relevansinya dalam Menghadapi Era Society 5.0 - Herman Darmawan; Abdul Qadir; Ahmad Khairani; Hifdzul Malik; Ardiyan Fikrianoor (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The moral degradation that occurs today often stems from several problems. Among other things, we can see many phenomena that occur today or based on data obtained from several survey agencies about the rampant behavior that leads to moral degradation, the cause of which is due to internal education and external influences. So this research was born which aims to provide theoretical and practical knowledge to scholars and the younger generation who will continue a relay of life. Through the understanding that exists in the book of 'Izhatun Nâsyi'în. This research uses a type of literature research, with a philosophical and historical approach. Data collection techniques use literature review and documentation. Then the data analysis technique uses Content Analysis. Based on the findings, it shows that the pattern of thought of Sheikh Musthafa al-Ghalayain is towards rationalism and fundamentalism. The values of character education in the book of 'Izhatun Nâsyi'în include: simplicity, glory of the soul, sociality, modernity, love of the homeland, change (reform), leadership and finally responsibility, all of which values are very relevant to the conditions that exist today, welcoming the era of society 5.0.